PnF (PLAY and FUN) APPLICATION FOR READING - Umaydah, Azizah; Wulandari, Fitri; Kurniati, Kurniati (Jurnal Smart, 2023)
In digitalization era the Indonesia students especially for junior high school must be able to use technology in learning process. This article is to investigation were: students lack in, students need, student wants in Reading. The current research used RnD (Research and Development) research. The respondent were student of elementary school. The result of this research is a PnF (Play and Fun) application, it is a mobile application that can use anywhere. In this application, the researcher only focus on Profession material. Based on the evaluation material, students can develop their reading skill using PnF (Play and Fun) Application